Variations of bronchial artery origin in 600 patients: Systematic analysis with multidetector computed tomography and digital subtraction angiography. Issue 22 (4th June 2021) - Choi, Won Seok; Kim, Min Uk; Kim, Hyo-Cheol; Yoon, Chang Jin; Lee, Jae Hwan
Abstract : Abstract: To identify and evaluate the spectrum and prevalence of variations in bronchial artery (BA) origin by multidetector computed tomography (MDCT) and digital subtraction angiography (DSA) in a large population with hemoptysis. From July 2008 to June 2015, data from 600 individuals with hemoptysis who underwent MDCT and DSA were retrospectively analyzed. The pattern of BA origin was investigated and classified according to distribution. A total of 1674 BAs were evaluated, 866 were right BA and 808 were left BA. Most BAs originated from the upper descending thoracic aorta, classified as orthotopic origin (n = 1464, 87.5%). Among ectopic origin BAs (n = 210, 12.5%), concavity of the aortic arch was the most common (n = 107). The most common distribution pattern was a single artery in each side (n = 262). According to our classification, Type I was most common (n = 457), including BAs originating in orthotopic fashion from the descending thoracic aorta. Type II (n = 2) was defined as BAs originating from the aortic arch or ascending aorta. Type III (not found) was defined as BAs originating from subclavian arteries, common carotid arteries, and their branch vessels. Type IV (n = 92) was Type I and II combined, Type V (n = 41) was Type I and III combined, Type VI (not found) was Type II and III combined, and Type VII (n = 8) was Type I, II, and III combined. Variations of BA origin could be systematically described in detail.